EFEKTIVITAS MEDIA POP-UP BOOK TERHADAP PENANAMAN NILAI AGAMA ANAK USIA 5-6 TAHUN DI TK KHADIJAH 36 KEBUNREJO GENTENG TAHUN PELAJARAN 2019-2020 - Nurul Ilmiyah; Ellyana Ilsan Eka Putri; Riris Wahyuningsih (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This study aims to examine the effectiveness of Pop-Up Book media on the cultivation of religious values for children aged 5-6 years. The problem in this research is whether Pop-Up Book Media is effective in instilling Religious Values in children aged 5-6 years? Can children understand religious values through Pop-Up Book media? Based on preliminary observations in the research location, it is known that the cultivation of religious values in children aged 5-6 years is in the good category. The object of this research is the principal, teachers and students of group B2 TK Khadijah 36 Genteng. The data collected in this study were obtained through observation, interview and documentation methods. Data analysis techniques used qualitative data analysis (data reduction, data display and drawing conclusions). The results of this study indicate that the Pop-Up Book media used in the learning of Inculcating Religious Values in children aged 5-6 years at TK Khadijah 36 Genteng is very effective, this is evidenced by the contents of the Pop-Up Book that can move when the page is opened as well as pictures 2-3 dimensions that attract attention make children interested and focus on capturing (absorbing) every message of Religious Value contained in the Pop-Up Book media, so that children can apply them in everyday life both at school and at home.